Penerapan Algoritma Batchelor-Wilkins dalam Pengklasteran Graf - Christyan Tamaro Nadeak (Indonesian Journal of Applied Mathematics, 2023)
Batchelor-Wilkins Algorithm is a simple and heuristic clustering algorithm used when the number of classes is unknown. In this paper we will use Batchelor-Wilkins algorithm in graph clustering, specifically a Banana Tree Graph B(n,k), a graph obtained by connecting one leaf of each of n copies of a complete bipartite graph K_{1,k-1} to a single root vertex.